ORIGIN AND PHYLOGENETIC EVOLUTION OF WHEAT (TRITICUM L.) CYTOGENETIC AND EVOLUTIONARY ASPECTS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines modern perspectives on the origin and evolutionary path of cultivated wheat. Particular attention is paid to the processes of natural hybridization and polyploidy, which led to the formation of modern genomes. The classification of species based on their ploidy and genomic composition is provided. The role of wild relatives in breeding adaptive varieties for the conditions of Uzbekistan is analyzed.